THE OLD IRISH POET: MAGICIAN, SEER OR STORYTELLER - Daria A. Ilgova (Russian Studies in Culture and Society)
The purpose of the study is to consider the structure of Old Irish poetry by the example of several principles of its division: by time, the function of the poet and the addressee of the poetic message.